(NbIBLIOTEKA (B"(NoGONEK(B". (NoTE^ESTWENNAQ KLASSIKA(B:s (NsOBRANIE SO^INENIJ W DWENADCATI TOMAH (B/s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NpRAWDA(B,s, 1984)
(NsOBRANIE SO^INENIJ W (B12-(NI TOMAH(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NpOWESTI I RASSKAZYs; (NdRAMAs